H2: the benchmark molecule for ultrafast science and technologies. (26th January 2018) - Ibrahim, Heide; Lefebvre, Catherine; Bandrauk, André D; Staudte, André; Légaré, François
Abstract: This review article focuses on imaging and controlling ultrafast dynamics of the hydrogen molecule and its cation, initiated by ultrashort laser pulses. We discuss the mechanisms underlying these dynamics and theoretical methods to describe them. A broad variety of defining and influencing theoretical and experimental results is presented. We put special emphasis on the required experimental techniques, many of which have been developed in view of imaging the fastest of all nuclear dynamics.